2019
DOI: 10.21640/ns.v11i22.1680
|View full text |Cite
|
Sign up to set email alerts
|

Psychometric properties of the Desensitization to Violence Scale for Adolescents

Abstract: Introduction: Desensitization to violence is the result of exposure to violence. It reduces the negative emotions in cognitive and physiological responses to violence and can even generate a positive response to it.Method: A mixed sequential method yielding a transactional analytic design for Exploratory Factor Analysis and Confirmatory Factor Analysis with a sample of 1720 participants of 25 different high schools and a juvenile detention center. Followed by convergent validity (as a criterion validit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 24 publications
0
1
0
Order By: Relevance
“…Studies have shown how platforms such as Twitter and Facebook frequently contain comments and images that can be considered as violence against women and those with certain sexual orientations; sexual violence is also prevalent in social media, and occurs on and through instant communication apps (Vyawahare & Chatterjee, 2020). Being constantly immersed in social networks, sharing messages, and surfing the Internet considerably increases the probability of observing OGV, which may reduce the emission of necessary signals such as negative emotions and cognitions (Galán-Jiménez et al, 2019) to activate awareness of its occurrence. In line with our results, greater exposure to, and a more problematic relationship with, smartphones would increase desensitization and normalization, such that awareness of this type of violence would be reduced.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown how platforms such as Twitter and Facebook frequently contain comments and images that can be considered as violence against women and those with certain sexual orientations; sexual violence is also prevalent in social media, and occurs on and through instant communication apps (Vyawahare & Chatterjee, 2020). Being constantly immersed in social networks, sharing messages, and surfing the Internet considerably increases the probability of observing OGV, which may reduce the emission of necessary signals such as negative emotions and cognitions (Galán-Jiménez et al, 2019) to activate awareness of its occurrence. In line with our results, greater exposure to, and a more problematic relationship with, smartphones would increase desensitization and normalization, such that awareness of this type of violence would be reduced.…”
Section: Discussionmentioning
confidence: 99%